Non-covalent Methods of Engineering Optical Sensors Based on Single-Walled Carbon Nanotubes - Gillen, Alice J.; Boghossian, Ardemis A. (Frontiers in Chemistry, 2019)
Optical sensors based on single-walled carbon nanotubes (SWCNTs) demonstrate tradeoffs that overall limit their use in in vivo and in vitro environments. Sensor characteristics are primarily governed by the non-covalent wrapping used to suspend the hydrophobic SWCNTs in aqueous solutions. Whereas sensors based on surfactant wrappings can show enhanced quantum efficiency, high stability, and diminished selectivity, sensors based on biopolymer wrappings conversely tend to show lower quantum efficiency and stability, while demonstrating improved selectivity. The majority of efforts to date have focused on optimizing sensors based on DNA wrappings, which have intermediate properties that can be improved through synthetic modifications. Additional wrappings based on synthetic alternatives, such as artificial heteropolymers, have also been used to circumvent the limitations of traditional surfactant- and biopolymer-based wrappings. In this review, we compare the advantages and disadvantages of most common wrappings and discuss ongoing endeavors in improving the specificity of non-selective wrappings based on DNA and synthetic polymers.